Efficacy of pneumatic displacement with 40-degree downward gaze positioning for treatment of submacular hemorrhage: report of two cases - Nakajima M (Dove Medical Press, 2012)
Masami Nakajima, Hiroshi Aso, Kohki NakayasuDepartment of Ophthalmology, Division of Visual Science, Nihon University School of Medicine, Tokyo, JapanBackground: Two retrospective case reports are described showing the efficacy of pneumatic displacement with 40-degree downward gaze positioning for treatment of submacular hemorrhage. Case 1 involved an 85-year-old woman who visited our clinic with a complaint of blurred vision in her right eye. Best corrected visual acuity (BCVA) of the right eye was hand motion. Her right eye showed a submacular hemorrhage with retinal macroaneurysm. Prone positioning was difficult because of the patient’s age and obesity. The treatment method was pneumatic displacement with 40-degree downward gaze positioning after intravitreal injection of 100% sulfur hexafluoride gas. After the treatment, the hemorrhage moved downward and BCVA of her right eye was 0.1. Case 2 involved a 58-year-old man with a complaint of blurred vision in his left eye. BCVA of his left eye was 0.3 and submacular hemorrhage was observed. He underwent displacement of the hemorrhage as previously described. After treatment, the submacular hemorrhage moved downward. Angiography detected a polypoidal lesion with a vascular network. upon diagnosis of polypoidal choroidal vasculopathy, bevacizumab was injected intravitreally. Two months after gas injection, the submacular hemorrhage disappeared. Optical coherence tomography showed flattening of the submacular retinal pigment epithelium, which was not observed prior to bevacizumab therapy. BCVA of the patient’s left eye was 0.9. Pneumatic displacement with 40-degree downward gaze positioning after intravitreal sulfur hexafluoride injection is useful to displace a submacular hemorrhage. Early application of this treatment provides improvement of vision and facilitates fundus examination, which could reveal the cause of the submacular hemorrhage.Keywords: 40-degree downward gaze position, submacular hemorrhage, intravitreal gas injection, sulfur hexafluoride, perfluoropropane